Equine grass sickness. (20th April 2014) - Pirie, R. S.; Jago, R. C.; Hudson, N. P. H.
Summary Equine grass sickness (EGS; equine dysautonomia) is a polyneuronopathy affecting both the central and the peripheral nervous systems of horses. As the name implies, EGS almost exclusively affects grazing horses, resulting in the development of a characteristic array of clinical signs, most of which can be attributed to neuronal degeneration in the autonomic and enteric nervous systems. Varying disease severities occur, largely determined by the extent of neuronal degeneration in the myenteric and submucous plexuses of the enteric nervous system. Extensive neuronal degeneration, as seen in acute and subacute forms of EGS, results in intestinal dysmotility, the severity of which is incompatible with survival. In comparison, a proportion of chronic forms of EGS, characterised by less severe neuronal degeneration, will survive. Despite extensive research efforts since EGS was first reported over 100 years ago, the precise aetiology remains elusive. This article reviews much of the scientific literature on EGS, covering epidemiology, pathology, diagnosis, treatment and aetiological hypotheses.